Vascular regulation of adult neurogenesis under physiological and pathological conditions - Sawada, Masato; Matsumoto, Mami; Sawamoto, Kazunobu (Frontiers in Neuroscience, 2014)
Neural stem cells in the mammalian adult brain continuously produce new neurons throughout life. Accumulating evidence in rodents suggests that various aspects of adult neurogenesis, including the genesis, migration, and maturation of new neurons, are regulated by factors derived from blood vessels and their microenvironment. Brain injury enhances both neurogenesis and angiogenesis, thereby promoting the cooperative regeneration of neurons and blood vessels. In this paper, we briefly review the mechanisms for the vascular regulation of adult neurogenesis in the ventricular-subventricular zone under physiological and pathological conditions, and discuss their clinical potential for brain regeneration strategies.